PROFESIONALISME GURU DALAM PEMBELAJARAN SKI UNTUK MENINGKATKAN MINAT BELAJAR SISWA MI - Risma Risma Wafiyun Ni'mah; Rizky Putri Fadillah Rizky Putri; munawwir munawwir (Alpen: Jurnal Pendidikan Dasar, 2026)
This study was motivated by the low level of student interest in the Islamic Cultural History (SKI) course at the Madrasah Ibtidaiyah, which is attributed to a monotonous teaching approach with little variation. The study aims to analyze the role of teacher professionalism in enhancing students’ interest in the SKI course. The approach employed is a literature review using a descriptive qualitative method. Data collection was conducted through document analysis of various relevant journals, which were then processed through the stages of data collection, data reduction, data presentation, and verification. The results indicate that teacher professionalism plays a crucial role in increasing students’ interest in learning. Teachers who possess high competence in implementing diverse teaching methods, utilizing attractive learning media, and creating an interactive learning environment successfully increase student engagement and enthusiasm. Thus, the higher the level of teacher professionalism, the greater the students’ interest in SKI learning.